Compartmentalization of pro-inflammatory cytokine levels in renal-transplanted pregnant women. (October 2013) - Correa-Silva, Simone; Prado, Karen Matias do; Oliveira, Leandro Gustavo; Ono, Erica; Camara, Niels Olsen Saraiva; Bevilacqua, Estela
Abstract Objective: We evaluated whether chronic exposure to immunosuppression in transplant recipients modulate the placental inflammatory cytokine levels associated to gestational tolerance mechanisms. Methods: Serum samples were collected from 12 renal transplanted pregnant under immunosuppressive regimen treatment and 10 healthy women in second/third trimester of gestation. Term placental tissues (decidua and chorionic villi) were also obtained after elective caesarean. Serum IL-1β, IL-6, IL-8, IL-12p70 and TNF-α were measured, as also in placental homogenates, by Cytometric Bead Array (CBA) combined with flow cytometry and, TGF-β and IL-18 were measured by ELISA. Results: Serum levels of IL-6 (p = 0.0001) and TNF-α (0.0112) were higher in the 2nd and 3rd trimesters and in decidua the spectrum of increased pro inflammatory cytokines was wider: IL-1β (p = 0.0001), IL-6 (p = 0.0001), IL-8 (p = 0.0001), IL-12p70 (p = 0.0001), TGF-β (p = 0.0089) and TNF-α (p = 0.0002). TGF-β1 was particularly increased in decidual compartment (p = 0.001). In the chorionic villous, pro inflammatory profile also were maintained. High IL-1β (p = 0.0001), IL-6 (p = 0.0001), IL-8 (p = 0.0001) and TNF-α (p = 0.0001) levels establish a similar pattern to that seem in decidua. Conclusion: Immunosuppressors may impair the immune response, but when associated with pregnancy the cytokine levels seems to shift a proinflammatory profile in placental compartments, which might also impact on the gestational outcomes in transplanted mothers.